2019
DOI: 10.1177/1049909119878446
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospice on Spending and Utilization Among Patients With Lung Cancer in Medicare

Abstract: Objectives: To compare patterns and understand drivers of spending and utilization by month in the last 6 months of life between patients with lung cancer who used hospice versus those who did not. Study Design: Retrospective cohort analysis using 2009 to 2013 Medicare claims. Methods: We used a 10% random sample of Medicare fee-for-service beneficiaries with lung cancer who died between 2010 and 2013 (43 789 beneficiaries). Patients were assigned to 2 groups depending on whether they used hospice care in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…3 A recent study by Kalidindi et al found that Medicare decedents with lung cancer who used hospice had significantly lower health-care spending than nonusers in the last 6 months of life, with most of the difference occurring in the final month of life. 4 This finding was consistent with studies of hospice use among patients with other conditions. 5,6 However, one limitation of these prior studies was that that they did not distinguish between patients with different lengths of hospice enrollment; instead, they lumped together patients who used hospice for 6 months or more with those enrolled for less than a week.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…3 A recent study by Kalidindi et al found that Medicare decedents with lung cancer who used hospice had significantly lower health-care spending than nonusers in the last 6 months of life, with most of the difference occurring in the final month of life. 4 This finding was consistent with studies of hospice use among patients with other conditions. 5,6 However, one limitation of these prior studies was that that they did not distinguish between patients with different lengths of hospice enrollment; instead, they lumped together patients who used hospice for 6 months or more with those enrolled for less than a week.…”
supporting
confidence: 86%
“…5,6 However, one limitation of these prior studies was that that they did not distinguish between patients with different lengths of hospice enrollment; instead, they lumped together patients who used hospice for 6 months or more with those enrolled for less than a week. A second limitation of prior work was that cost savings were estimated over long time intervals-such as last year of life, 5,6 last 6 months, 4 or last month, 7 while the median length of hospice use was only 17 days, and the average length of stay was around 88.2 days. 8 Given the variation in length of hospice enrollments, useful assessments of hospice savings must: (1) consider the patient's actual length of hospice stay, and (2) use the period during which hospice is actually used for cost comparisons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with terminal cancer were more likely to present to ED in the evenings, overnight or at the weekends, outwith usual business hours 19,28 . There was consistent evidence (5 studies) demonstrating that cancer decedents who were close to death were significantly more likely to use unscheduled care than those who were not close to death 9,16,30,34,35 .…”
Section: Temporalmentioning
confidence: 80%
“…There was a significant amount of consistent evidence supporting the association between hospice enrolment and unscheduled care use by cancer decedents (12 studies). Being enrolled in a hospice programme was consistently associated with a lower use of unscheduled care 5,7,15,18,34,[37][38][39] . Some studies found that hospice enrolment was involved in a 1.5-2 fold decrease in ED attendances 13,37,38 .…”
Section: Enrolment In Hospice Programmementioning
confidence: 99%